Cocrystals/salts of Furosemide : Interesting case of colour cocrystal polymorphism - Sangtani, Ekta; Jha, Kunal; Munshi, Parthapratim; Gonnade, Rajesh (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Color cocrystal polymorphism; Sandwich assembly; Stacking interactions

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

Crystal structure of a 1:1 co-crystal of the anti-cancer drug gefitinib with azelaic acid - George, Christy P.; Sangtani, Ekta; Gonnade, Rajesh G. (Acta Crystallographica Section E: Crystallographic Communications, 2020)
In the title co-crystal, C22H24ClFN4O3·C9H16O4, gefitinib (GTB; systematic name: quinazolin-4-amine) co-crystallizes with azelaic acid (AA; systematic name: nona-nedioic acid). The co-crystal has the monoclinic P21/n centrosymmetric space group, containing one mol-ecule each of GTB and AA in the asymmetric unit. A structure overlay of the GTB mol-ecule in the co-crystal with that of its most stable polymorph revealed a significant difference in the conformation of the morpholine moiety. The significant deviation in the conformation of one of the acidic groups of azelaic acid from its usual linear chain structure could be due to the encapsulation of one acidic group in the pocket formed between the two pincers of GTB namely, the morpholine and phenyl moieties. Both GTB and AA mol-ecules form N-H⋯O, O-H⋯N, C-H⋯O hydrogen bonds with C-H⋯F close contacts along with off-stacked aromatic π-π inter-actions between the GTB mol-ecules.

Chemistry, anti-diabetic activity and structural analysis of substituted dihydropyrimidine analogues - Bairagi, Keshab M.; Younis, Nancy Safwat; Emeka, Promise Madu; Venugopala, Katharigatta N.; Alwassil, I, Osama; Khalil, Hany Ezzat; Sangtani, Ekta; Gonnade, Rajesh G.; Mohanlall, Viresh; Nayak, Susanta K. (Journal of Molecular Structure, 2021)
In an effort to identify an anti-diabetic agent, a series of methyl/ethyl 4-(hydroxyphenyl)-6-methyl-2-oxo/thioxo-1,2,3,4 tetrahydropyrimidine-5-carboxylate analogues (4a-h) have been synthesized, purified, and characterized by using Fourier-Transform Infrared Spectroscopy (FT-IR) and NMR (H-1 and C-13). The synthesized compounds were screened for anti-hyperglycemic activity using Streptozotocin (STZ) induced diabetic rat model. The anti-hyperglycemic activity of dihydropyrimidine (DHPM) compound is mainly analyzed with the variation of substituents present on the phenyl ring and urea/thiourea group on pharmacophoric features. Further, the crystal structure and supramolecular characteristics of two compounds 4c and 4f were analyzed through a single-crystal X-ray method and the Hirshfeld Surface Analysis, which shows hydrogen bonding through N-H center dot center dot center dot O and N-H center dot center dot center dot S interactions with the formation of ring motif in the crystal structure. It is interesting to note that among the title compounds, the 4a, 4e, 4f, and 4g significantly displayed a better hypoglycemic effect in vivo rat model study. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dihydropyrimidine (DHPM); Hypoglycemia; Streptozotocin (STZ); Type-2 diabetes mellitus (T2DM)